Recurrent ovarian malignancy presenting as cutaneous metastasis - Karpate Shilpaja; Samal Swarnlata; Jain Suchi (Wolters Kluwer Medknow Publications, 2009)
Cutaneous metastasis from ovarian carcinoma is relatively uncommon in clinical practice. We report the case of the woman who presented to us with clitoral nodules and skin nodules. Histopathological examination of nodules confirmed the diagnosis of metastasis of an ovarian carcinoma. Despite poor prognosis, the patient responded and survived well beyond the expected four months survival of similar cases.